Safety, Tolerability, and Pharmacokinetics of the Broadly Neutralizing Human Immunodeficiency Virus (HIV)-1 Monoclonal Antibody VRC01 in HIV-Exposed Newborn Infants. (4th November 2019) - Cunningham, Coleen K; McFarland, Elizabeth J; Morrison, R Leavitt; Capparelli, Edmund V; Safrit, Jeffrey T; Mofenson, Lynne M; Mathieson, Bonnie; Valentine, Megan E; Perlowski, Charlotte; Smith, Betsy; Hazra, Rohan; Purdue, Lynette; et al.
Abstract: Background: Although mother-to-child human immunodeficiency virus (HIV) transmission has dramatically decreased with maternal antiretroviral therapy, breast milk transmission accounts for most of the 180 000 new infant HIV infections annually. Broadly neutralizing antibodies (bNAb) may further reduce transmission. Methods: A Phase 1 safety and pharmacokinetic study was conducted: a single subcutaneous (SC) dose of 20 or 40 mg/kg (Dose Groups 1 and 2, respectively) of the bNAb VRC01 was administered to HIV-exposed infants soon after birth. Breastfeeding infants (Dose Group 3) received 40 mg/kg SC VRC01 after birth and then 20 mg/kg/dose SC monthly. All infants received appropriate antiretroviral prophylaxis. Results: Forty infants were enrolled (21 in the United States, 19 in Africa). Subcutaneous VRC01 was safe and well tolerated with only mild-to-moderate local reactions, primarily erythema, which rapidly resolved. For multiple-dose infants, local reactions decreased with subsequent injections. VRC01 was rapidly absorbed after administration, with peak concentrations 1–6 days postdose. The 40 mg/kg dose resulted in 13 of 14 infants achieving the serum 50 micrograms (mcg)/mL target at day 28. Dose Group 3 infants maintained concentrations greater than 50 mcg/mL throughout breastfeeding. Conclusions: Subcutaneous VRC01 as single or multiple doses is safe and well tolerated in very young infants and is suitable for further study to prevent HIV transmission in infants. Abstract : Safety and pharmacokinetics of VRC01, a broadly neutralizing monoclonal antibody, was evaluated in HIV-exposed neonates. VRC01 was well tolerated with frequent mild local reactions. Birth dose of 40 mg/kg and monthly dose of 20 mg/kg achieved target trough serum levels.